GREEN ENERGY LITERACY: A REVIEW AND BIBLIOMETRIC ANALYSIS - Iman Gudiman; Irvan Permana; Didit Ardianto (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2023)
Research on the importance of energy literacy has increased, this can be seen from the many articles that have been studied on this theme. Increased attention to the importance of energy literacy is related to the influence of the quality of energy literacy of citizens of a country which directly impacts the good or bad quality of the environment due to climate change. This study aims to evaluate the most relevant themes related to Energy Literacy based on bibliometric analysis, with input using the keywords "Energy Literacy" or "Green Energy Literacy". The data used is based on the Google Scholar database using the Pop (Publish or Perish) search engine software, this data is then stored in a Research Information System (RIS) format for further analysis. The data in RIS format was then analyzed using VOSviewer software to visualize networks consisting of authors, year of publication, publisher's journal name, and citations. Analysis conducted in October 2021 found a total of 100 documents in the 2016-2021 period. The results showed that in the last five years there were four publishers that published the most articles on the topic Green energy Literacy, namely elsevier with a total of 20 articles followed by Taylor & Francis, iopscience and Springer. Keyword analysis shows that the study of Green Energy Literacy is closely related to the themes of student, study, school, knowledge, behavior, attitude, awareness, and effect. Overall the data from this bibliometric analysis makes it possible to answer the question of what are the research trends in the field of Green energy Literacy in the last 5 years.